The influence of copper(II) ions on wool photostability in the dry state. (17th June 2013) - Zhang, Hu; Deb‐Choudhury, Santanu; Plowman, Jeffrey; Millington, Keith; Dyer, Jolon
Abstract : It has been hypothesised that the presence of trace metals in wool, notably copper and iron, has an influence on the formation of free radicals under irradiation and thereby affects the photostability of wool and wool products, particularly in the wet state. There has been limited research evaluating the influence of copper ions on wool photodiscoloration. This study examined the relative photodiscoloration of wool bound with varied amounts of copper(II) ions under UVA, UVB and blue light irradiation in the dry state. Total reflectance and visible/near‐infrared absorbance spectra, tryptophan‐type fluorescence ( λ ex = 295 nm, λ em = 340 nm) and photoinduced chemiluminescence emissions of natural wool and copper(II)‐treated wool were characterised and contrasted. CIELAB colour space, D1925 yellowness and CIE whiteness values measured from irradiated wool samples indicate that wool treated with copper(II) solution at a higher concentration yellowed faster and experienced greater overall colour changes under UVA and UVB irradiation, whereas copper(II)‐treated wool seemed to be more photostable than untreated natural wool under blue light irradiation. It was also observed that binding copper ions to wool resulted in decreased tryptophan‐type fluorescence and photoinduced chemiluminescence emissions relative to untreated natural wool.